2016
DOI: 10.1111/jth.13479
|View full text |Cite
|
Sign up to set email alerts
|

Low ADAMTS‐13 activity and the risk of coronary heart disease – a prospective cohort study: the Rotterdam Study

Abstract: Background The metalloprotease ADAMTS-13 cleaves high-molecular-weight von Willebrand factor multimers into smaller, less procoagulant forms. Low ADAMTS-13 activity is associated with an increased risk of ischemic stroke but its pathogenic role in coronary heart disease (CHD) is unclear. Objectives We aimed to determine the association between ADAMTS-13 activity and the risk of CHD in a large prospective population-based cohort study. Methods A total of 5688 participants of the Rotterdam Study, a population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 28 publications
3
34
1
2
Order By: Relevance
“…79 More recently, it was reported that in those without a history of CAD who were followed for approximately a decade, lower levels of plasma ADAMTS13 activity were associated with higher rates of incident coronary events and cardiovascular mortality. 62,63 Activity of ADAMTS13 was more predictive than VWF antigen levels, thereby reinforcing the idea that examination of plasma VWF concentrations may not reflect regulatory processes occurring at the blood poolendothelial interface.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…79 More recently, it was reported that in those without a history of CAD who were followed for approximately a decade, lower levels of plasma ADAMTS13 activity were associated with higher rates of incident coronary events and cardiovascular mortality. 62,63 Activity of ADAMTS13 was more predictive than VWF antigen levels, thereby reinforcing the idea that examination of plasma VWF concentrations may not reflect regulatory processes occurring at the blood poolendothelial interface.…”
mentioning
confidence: 65%
“…61 Conversely, in large trials in those with atherosclerotic risk factors but without acute coronary syndrome, circulating levels of VWF are only modestly associated with risk for future atherosclerotic events or cardiac mortality. [61][62][63] These data would seem to argue that VWF becomes functionally important only in late atherothrombotic complications. However, circulating levels of VWF do not necessarily reflect events that occur at the blood pool-endothelial interface or the relative proportion of VWF in ultralarge multimers.…”
Section: Role Of Vwf In Atherogenesismentioning
confidence: 94%
“…В то же время, по данным исследования M.A.H. Sonneveld и соавт., vWF и ADAMTS-13 представляют собой отдельные независимые факторы риска неблагоприятных исходов ИБС [43]. Необходимо подчеркнуть, что дисбаланс vWF и его ингибитора в условиях воспаления (в т.ч., неспецифического) и метаболических нарушений (СД, метаболический синдром) оказывает прокоагулянтный эффект [44,45].…”
Section: Markers Of Endothelial Dysfunction маркеры эндотелиальной диunclassified
“…5 Previously, large population-based studies have demonstrated an association between lower ADAMTS13 activity with myocardial infarction and stroke. 6,7 Remission ADAMTS13 activity after recovery from acute iTTP is an attractive candidate as a biomarker and therapeutic target to improve long-term outcomes in all patients with iTTP.…”
Section: University Of Pennsylvaniamentioning
confidence: 99%